1976
DOI: 10.1007/bf00341732
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antibiotic resistance plasmid ERL1 from Streptococcus pyogenes

Abstract: The streptococcal plasmid ERL1 determining inducible resistance to erythromycin, lincomycin, and staphylomycin S was isolated by dye-buoyant density centrifugation and shown to have a molecular weight of about 17.5 Mdal, as revealed by sedimentation through neutral sucrose gradients. In SM60 cells entering the stationary phase its covalently closed circular form was present to the extent of 5 copies per chromosomal genome equivalent, ERL1 was subject to the DNA restriction and modification mechanism discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The molecular sizes of the plasmids in M439 and M403 differ from those found for drug resistance plasmids in other streptococci (4,5,6,14,17). The conjugative Em resistance plasmids studied here exhibit coresistance to macrolides other than Em and to lincomycin, clindamycin, factor S of virginiamycin, and pristinamycin Ia.…”
Section: Downloaded Frommentioning
confidence: 51%
“…The molecular sizes of the plasmids in M439 and M403 differ from those found for drug resistance plasmids in other streptococci (4,5,6,14,17). The conjugative Em resistance plasmids studied here exhibit coresistance to macrolides other than Em and to lincomycin, clindamycin, factor S of virginiamycin, and pristinamycin Ia.…”
Section: Downloaded Frommentioning
confidence: 51%
“…In several cases, the molecular masses of these plasmids are similar, with plasmid DNA being of a size of approximately 17 megadaltons (6,9,13,26). In one case we showed that plasmid pAM,8l from S. faecalis strain DS-5 was approximately 95% homologous with a plasmid of similar size in S. pyogenes strain AC-1 (36 …”
mentioning
confidence: 70%
“…Strain H46A cells were lysed with mutanolysin (Dainippon Pharmaceutical, Osaka, Japan), and chromosomal DNA was treated with phenol and further purified by CsCl density gradient centrifugation (18). The average size of this DNA was 50 kilobases (kb).…”
Section: Methodsmentioning
confidence: 99%